2003
DOI: 10.1086/378196
|View full text |Cite
|
Sign up to set email alerts
|

High‐Precision Limb‐Darkening Measurement of a K3 Giant Using Microlensing

Abstract: We obtain high-precision limb-darkening measurements in five bands (V , V E , I E , I, and H) for the K3 III (T eff = 4200 K, [Fe/H]= +0.3, log g = 2.3) source of the Galactic bulge microlensing event EROS BLG-2000-5. These measurements are inconsistent with the predictions of atmospheric models at > 10 σ. While the disagreement is present in all bands, it is most apparent in I, I E and V E , in part because the data are better and in part because the intrinsic disagreement is stronger. We find that when limb-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
5
61
0
Order By: Relevance
“…Article published by EDP Sciences and available at http://www.aanda.org or http://dx.doi.org/10.1051/0004-6361:20040112 giants and sub-giants (Fields et al 2003 and references therein) and a main sequence star (Abe et al 2003). A new generation of stellar atmosphere models (Orosz & Hauschildt 2000) have revealed limb-darkening laws that are significantly different from the traditional analytic ones (Bryce et al 2002;Claret & Hauschildt 2003).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Article published by EDP Sciences and available at http://www.aanda.org or http://dx.doi.org/10.1051/0004-6361:20040112 giants and sub-giants (Fields et al 2003 and references therein) and a main sequence star (Abe et al 2003). A new generation of stellar atmosphere models (Orosz & Hauschildt 2000) have revealed limb-darkening laws that are significantly different from the traditional analytic ones (Bryce et al 2002;Claret & Hauschildt 2003).…”
Section: Letter To the Editormentioning
confidence: 99%
“…An et al (2002) and Fields et al (2003) constrained non-linear limb-darkening relations from microlensing observations of a K3 giant and compared them to model stellar atmospheres. They found significant disagreement between the observed and predicted limb-darkening relation.…”
Section: Introductionmentioning
confidence: 99%
“…fit model intensity profiles to interferometric observations from Wittkowski et al (2004) and predicted similar fundamental parameters as those authors. Also, Neilson & Lester (2011) predicted limb-darkening coefficients for a specific limb-darkening law from spherical models, compared them to results for microlensing observations from Fields et al (2003), and found better agreement than the authors did using plane-parallel models and spherical models that had intensity profiles clipped to remove the extended limb.…”
Section: Stellar Atmosphere Code and Limb-darkening Lawsmentioning
confidence: 99%